2019
DOI: 10.1021/acssynbio.8b00411
|View full text |Cite
|
Sign up to set email alerts
|

Knock-In Strategy for Editing Human and Zebrafish Mitochondrial DNA Using Mito-CRISPR/Cas9 System

Abstract: The mitochondria DNA (mtDNA) editing tool, zinc finger nucleases (ZFNs), transcription activator-like effector nuclease (TALENs), and clustered regularly interspaced short palindromic repeats/CRISPR associated protein 9 (CRISPR/Cas9) system, is a promising approach for the treatment of mtDNA diseases by eliminating mutant mitochondrial genomes. However, there have been no reports of repairing the mutant mtDNA with homologous recombination strategy to date. Here, we show a mito-CRISPR/Cas9 system that mito-Cas9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 59 publications
4
46
0
2
Order By: Relevance
“…Unsurprisingly, there are many known mechanisms of protein transport into different mitochondrial subcompartments (Pfanner et al, 2019). We (Orishchenko et al, 2016) and others (Jo et al, 2015;Loutre et al, 2018;Bian et al, 2019) have demonstrated that introduction of a mitochondrial localization signal at the N-terminus of Cas9 leads to an effective Cas9 import into mitochondrial matrix. Therefore, protein component of CRISPR/Cas9 system could be imported inside mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, there are many known mechanisms of protein transport into different mitochondrial subcompartments (Pfanner et al, 2019). We (Orishchenko et al, 2016) and others (Jo et al, 2015;Loutre et al, 2018;Bian et al, 2019) have demonstrated that introduction of a mitochondrial localization signal at the N-terminus of Cas9 leads to an effective Cas9 import into mitochondrial matrix. Therefore, protein component of CRISPR/Cas9 system could be imported inside mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…To help explain this surprising result, the authors present data showing that the CRISPR/Cas9 system appears to significantly upregulate several of the major proteins involved in nuclear DNA repair. 66 Once again, however, the precise mechanism remains unclear. Most critically, it has not been clearly demonstrated that the nuclear DNA repair enzymes are even imported into the mitochondria, nor that they can effectively assemble and operate properly within the mitochondrial matrix, which would be an obvious mechanistic prerequisite for any homologous recombination events to be able to occur.…”
Section: Mitochondrial Replacement Therapy (Mrt)mentioning
confidence: 99%
“…Three primers, F1 (5' TCTATTCATCGTCTCGGAAG 3'), F2 (5' TACC ATTCCTAACAGGGTTC 3') and R (5' TTTATGGGTGTAATGCGGTG 3'), were synthesized by the Beijing Genomics Institute (Beijing, China). Primer F1/R was used to amplify the deleted mtDNA fragment, while F2/R to wild-type mtDNA sequence [43,44]. All of the three primers were added to the reaction system for PCR.…”
Section: Quantification Of Deleted Mtdna In Aged Micementioning
confidence: 99%